Progress in pattern recognition, image analysis, computer vision, and applications : 22nd Iberoamerican Congress, CIARP 2017, Valparaíso, Chile, November 7-10, 2017, Proceedings /: 22nd Iberoamerican Congress, CIARP 2017, Valparaíso, Chile, November 7-10, 2017, Proceedings. (2018) - Unknown
No abstract available